MARRIAGE COMMUNICATION PATTERNS FOR UNDERAGE COUPLES: (Case Study in Jamur Gele Village, Putri Betung District Gayo Lues Regency) - Nurhayati (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This study aims to determine the form of communication of underage married couples, as well as to find out the inhibiting and supporting factors in the communication of underage marriage couples and to determine the impact of communication patterns of underage marriage couples on household continuity in Jamur Gele Village, Putri Betung District, Gayo Lues Regency. This type of research is descriptive qualitative research. Descriptive qualitative format is very appropriate to be used to examine problems that require in-depth study, such as the problem of consumer behavior in a product, the problem of the viewer's view of the effects of media on a show, problems in the implementation of public policy in the community and its surroundings. Data collection was done by interviews and documentation. The results of this study indicate that communication of young couples in Jamur Gele Village uses forms of communication, verbal, nonverbal (body language), through intermediaries (by third parties), and communicating if there is a goal to be achieved. Meanwhile, supporting factors for communication between young couples can also be seen from the way each couple communicates, economic factors are also important in building communication between young couples. As for the impact of this form of communication pattern for early marriage couples is caused by the choice of oral and non-verbal communication (body language).